Testofen® (Fenugreek extract) increases strength and muscle mass compared to placebo in response to calisthenics. A randomized control trial. Issue 4 (10th April 2020) - Rao, Amanda J.; Mallard, Alistair R.; Grant, Ross
Abstract : This randomised, placebo controlled, double‐blind study aimed to examine changes in muscular strength and endurance, body composition, functional threshold power, and sex hormones in response to an 8‐week calisthenic programme with daily supplementation with Testofen ® (Fenugreek extract) or a placebo. A total of 138 male participants (25‐47yrs) were enrolled and randomized to three equal groups: 600 mg Testofen ® /day, 300 mg Testofen ® /day or placebo. Muscle strength and endurance, functional threshold power, body composition, and sex hormones were measured at baseline, weeks 4 and 8. Participants completed a whole‐body calisthenic programme three times a week. All groups improved their maximal leg press from baseline to 8 weeks, however, both Testofen ® treated groups improved more than placebo ( P  < .05). The 600 mg group showed decreases in body mass of 1.2 kg, −1.4% body fat and an increase in lean mass (1.8%) at 8 weeks. The 600 mg group also demonstrated an increase in testosterone concentration from baseline to 8 weeks. This study indicates that Testofen ® may be an effective ergogenic aid for individuals wanting to rapidly improve their exercise performance capabilities and body composition above and beyond that of calisthenic exercise alone.